The new green consumer guide - Hailes, Julia (New York, 2007)
Green consumerism is on the rise, but many of us are confused by an avalanche of information - much of it conflicting. We want to do the right thing to help save energy and resources, but where can we start as everyday consumers? Can we do anything to make a difference? Julia Hailes, environmental expert and co-author of the original Green Consumer Guide (Gollancz, 1988), is adamant that we can. The New Green Consumer Guide is accessible and reader-friendly, addressing all the questions the general consumer is asking, giving authoritative advice on a wide range of issues, explaining which products, brands and companies are getting it right - and which ones are getting it wrong. With clearly presented sections on home and garden, food and drink, electrical goods and the office, plus travel, transport, fashion and cosmetics, it is written with today's lifestyles in mind. With full-colour pages and illustrations throughout, and with scores of tips, checklists and ideas, The New Green Consumer Guide offers real, affordable solutions to the world's most-talked-about challenge. It will be the only guide to greener living that busy consumers will need.